DIAGNOSTIC AND PROGNOSTIC MARKERS OF THE DIABETES MELLITUS TYPE 2 COURSE IN CONNECTION WITH ESSENTIAL ARTERIAL HYPERTENSION TAKING INTO ACCOUNT THE KIDNEY FUNCTION - Вірстюк, Н. Г.; Іквука, А. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In diabetes mellitus type 2 combined with essential hypertension, the risk of kidney failure increases by 15-20 times; the course of combined pathology is often accompanied by the development of heart f ailure. Therefore, it is important to have early diagnosis and monitoring of kidney damage and prediction of cardiac dysfunction. The aim of the research: Determination of additional diagnostic and prognostic markers of the course of diabetes mellitus type 2 in combination with essential hypertension, taking into account the function of the kidneys. Materials and methods: 75 patients were examined, including 25 patients with drug-compensated essential hypertension stage II, 25 patients with diabetes mellitus type 2 subcompensated and 25 patients with diabetes mellitus type 2 subcompensated combined with essential hypertension. Determination of carbohydrate metabolism based on assessment of glycated hemoglobin (HbA1C), blood lipid profile tests, kidney function tests e.t.c. were carried out. The content of the tumor necrosis factor alpha (TNF-α), N-terminus of the brain natriuretic peptide (NT-proBNP) induced by hypoxia factor-1 alpha (GIF-1α), connective tissue growth factor (CTGF) in blood and lipocaine (NGAL) in urine were determined using immunoassay method followed by statistical processing of the results. Results: In patients with DM2 combined with EH, there is a severe violation of kidney function with increasing albuminuria and a decrease in glomerular filtration rate (GFR). Correlation between increased albuminuria, reduced GFR, systolic blood pressure (SBP), HbA1C, total cholesterol (TC), triglycerides (TG) and low density lipoprotein (LDL) indicate the multifactorial process of kidney damage in patients with DM2 combined with EH and a high risk of cardiovascular diseases. An increase in the content of TNF-α, NT-proBNP, GIF-1α, CTGF in serum and lipocaine (NGAL) in urine in patients with hypertension, type 2 diabetes, and especially with combined pathology, were observed, which correlated with an increase in the albumin-creatinine index and decrease in GFR. Conclusions: In patients with type 2 diabetes, in combination with essential hypertension on the background of carbohydrate and lipid metabolism disorder, the development of nephropathy is characterized by an increase in the content of TNF-α, NT-proBNP, GIF-1α, blood FTP in the urine and lipocaine (NGAL) which can act as additional diagnostic and prognostic markers for the progression of combined pathology.